Crystal structure, shape analysis and bioactivity of new LiI, NaI and MgII complexes with 1, 10‐phenanthroline and 2‐(3, 4‐dichlorophenyl)acetic acid. Issue 3 (13th February 2019) - Shah, Syed Raza; Shah, Zarbad; Ullah, Najeeb; Hussain, Javid; Al-Harrasi, Rashid; Khan, Ajmal; Rawson, Jeremy M.; Al-Harrasi, Ahmed; Anwar, Muhammad U.
Abstract : Reactions of 1, 10‐phenanthroline (phen) and 2‐(3, 4‐dichlorophenyl)acetic acid (dcaH) with Mn (CO3 ) ( M = Li I, Na I and Mg II ; n = 1 and 2) in MeOH yield the mononuclear lithium complex, the dinuclear sodium complex and the one‐dimensional chain magnesium complex. In these complexes, phen binds via an N, N ′‐chelate pocket, while the deprotonated dca − ligands coordinate either in a monodentate or bidentate fashion. Abstract : Reactions of 1, 10‐phenanthroline (phen) and 2‐(3, 4‐dichlorophenyl)acetic acid (dcaH) with Mn (CO3 ) ( M = Li I, Na I and Mg II ; n = 1 and 2) in MeOH yield the mononuclear lithium complex aqua[2‐(3, 4‐dichlorophenyl)acetato‐κ O ](1, 10‐phenanthroline‐κ 2 N, N ′)lithium(I), [Li(C8 H5 Cl2 O2 )(C12 H8 N2 )(H2 O)] or [Li(dca)(phen)(H2 O)] (1 ), the dinuclear sodium complex di‐μ‐aqua‐bis[2‐(3, 4‐dichlorophenyl)acetato‐κ O ](1, 10‐phenanthroline‐κ 2 N, N ′)sodium(I), [Na2 (C8 H5 Cl2 O2 )2 (C12 H8 N2 )2 (H2 O)2 ] or [Na2 (dca)2 (phen)2 (H2 O)2 ] (2 ), and the one‐dimensional chain magnesium complex catena ‐poly[[[diaqua(1, 10‐phenanthroline‐κ 2 N, N ′)magnesium]‐μ‐2‐(3, 4‐dichlorophenyl)acetato‐κ 2 O : O ′] 2‐(3, 4‐dichlorophenyl)acetate monohydrate], [Mg(C8 H5 Cl2 O2 )(C12 H8 N2 )(H2 O)2 ](C8 H5 Cl2 O2 )·H2 O n or [Mg(dca)(phen)(H2 O)2 ](dca)·H2 O n (3 ). In these complexes, phen binds via an N, N ′‐chelate pocket, while the deprotonated dca − ligands coordinate either in a monodentate (in1 and2 ) or bidentate (in3 ) fashion. The remaining coordination sites around the metal ions are occupied by water molecules in all three complexes. Complex1 crystallizes in the triclinic space group P with one molecule in the asymmetric unit. The Li + ion adopts a four‐coordinated distorted seesaw geometry comprising an [N2 O2 ] donor set. Complex2 crystallizes in the triclinic space group P with half a molecule in the asymmetric unit, in which the Na + ion adopts a five‐coordinated distorted spherical square‐pyramidal geometry, with an [N2 O3 ] donor set. Complex3 crystallizes in the orthorhombic space group P 21 21 21, with one Mg 2+ ion, one phen ligand, two dca − ligands and three water molecules in the asymmetric unit. Both dcaH ligands are deprotonated, however, one dca − anion is not coordinated, whereas the second dca − anion coordinates in a bidentate fashion bridging two Mg 2+ ions, resulting in a one‐dimensional chain structure for3 . The Mg 2+ ion adopts a distorted octahedral geometry, with an [N2 O4 ] donor set. Complexes1 –3 were evaluated against urease and α‐glucosidase enzymes for their inhibition potential and were found to be inactive.